Estudios socio espaciales y vida cotidiana: ser y estar en el mundo. - Moreno Lache, Nubia; Vanzella Castellar, Sonia Maria (Anekumene, 2018)
Estudios socio espaciales y vida cotidiana: ser y estar en el mundo.